2015
DOI: 10.1590/1983-1447.2015.03.49670
|View full text |Cite
|
Sign up to set email alerts
|

Teaching in higher education in nursing: an integrative literature review

Abstract: It was found that there are numerous gaps in understanding the teaching activity in nursing. The concerns identified may offer help for understanding the teaching world and conceptions about being a teacher in nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 28 publications
(33 reference statements)
1
14
0
7
Order By: Relevance
“…However, to be a teacher requires more than to be a good professional. To be a teacher, is necessary to have specific competences that are beyond the skills required to be a good nurse (24)(25) . Postgraduate education stricto sensu develops qualified teachers and fosters scientific researches, aiming to qualify professional teachers for teaching and assistance professionals directed for the job market (26) .…”
Section: Discussionmentioning
confidence: 99%
“…However, to be a teacher requires more than to be a good professional. To be a teacher, is necessary to have specific competences that are beyond the skills required to be a good nurse (24)(25) . Postgraduate education stricto sensu develops qualified teachers and fosters scientific researches, aiming to qualify professional teachers for teaching and assistance professionals directed for the job market (26) .…”
Section: Discussionmentioning
confidence: 99%
“…(Fernanda) Another significant influence on the participants when they entered the teaching profession was living with experienced teachers in the context of work, which represented a professional training strategy for them through the exchanges and intergenerational sharing (3,5,17) . The relationship between teachers who are contemporaneous exist and therefore share the work at the same time but with different experiments since they are at different stages of the teacher professional life cycle (11) , as seen below: These considerations show how learning how to teach was influenced by previous experiences and while teaching, however, the complexity of the teaching activity requires investments in the enhancement of professionalism, especially in the aspects of pedagogical training (7,11,17) .…”
Section: [] I See Myself As Being Hard and Soft At The Same Time mentioning
confidence: 99%
“…Some studies (2)(3)(4)(5)(6) on the training of teachers and identity construction of nursing teachers in higher education, revealed that teachers seek changes related to their educational training mainly to fit the legal guidelines that propose the use of a more dialogical and integrated perspective, as opposed to the appreciation of technical and scientific education in this area of expertise. Although there is a trend to carry out pedagogical training focused on these faculty members, experiences and inspiration from those teachers considered remarkable are still used as the main source of teaching knowledge (2,4,7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In order to teach, the teaching nurse bases her teachings on her own experiences and the knowledge she seeks in the course of her experiences. 24 It is necessary to rethink the formation of both the student and the educator in such a way as to include the theme of death and mourning in the teaching of both. 25 From this point of view, it is evident that the discussions about this topic when they arise are presented in a fragmented, punctual and superficial way, which makes it difficult to expand understanding about death and dying, 26 pointing to an insufficient academic formation to collaborate with the development of care capacities at the end of the person's life.…”
mentioning
confidence: 99%